Observational Study Of Animal Slaughterhouses (RPH) Muaro Kumpeh Village Muaro Jambi - Pratiwi, Heni (Information Technology and Science (ITScience), 2024)
A slaughterhouse (RPH) is a building or building complex with certain designs and conditions used for slaughtering animals to produce safe, healthy, whole, and halal (ASUH) meat for consumption by the general public. This research aims to find out the process carried out by the RPH in carrying out its duties by Islamic law. In this research, the method used to analyze the Muaro Jambi Mandiri Enterprise RPH was to use literature review and observation methods to describe and explain the condition of the Mandiri Enterprise RPH in Muaro Kumpeh Village. The data used in this research uses primary data obtained directly through observation or interviews and secondary data. The data collection methods in this research are interviews and observations regarding the suitability of animal slaughtering, physical facilities, distribution of slaughtered products, and critical points. at this RPH. The study results show that this abattoir has carried out its business by Islamic law and has MUI halal certification. It was found that the critical point in this abattoir is in the place used for slaughtering animals, where the condition of the place is very at risk of unclean contamination.